Atomic Layer Deposition of MoSe2Nanosheets on TiO2Nanotube Arrays for Photocatalytic Dye Degradation and Electrocatalytic Hydrogen Evolution - Zazpe, Raul; Krumpolec, Richard; Sopha, Hanna Ingrid; Rodriguez Pereira, Jhonatan; Charvot, Jaroslav; Hromádko, Luděk; Kolíbalová, Eva; Michalička, Jan; Pavliňák, David; Motola, Martin; Přikryl, Jan; Krbal, Miloš; et al. (My University, 2020)
Herein, hierarchical MoSe2/1D TiO2 nanotube layer structure was successfully fabricated in a simple and fast fashion and its photocatalytic and electrocatalytic properties were assessed. The novelty of this work lies in the utilization of Atomic Layer Deposition (ALD) technique to deposit MoSe2 nanosheets on 1D TiO2 nanotube layers. The photoelectrochemical and photo- and electrocatalytic properties were explored and optimized as a function of the MoSe2ALD cycles. ALD allowed precise control on MoSe2 nanosheet size, and in turn, on the surface structure, which is pivotal for efficient catalysts. The MoSe2 nanosheets grew on both inner and outer 1D TiO2 nanotube surface mainly perpendicularly oriented, maximizing the exposed active edges, an essential aspect to fully exploit the MoSe2 photo- and electrochemical properties. Outstanding photo- and electrocatalytic activity were recorded in both dye organic pollutant degradation and hydrogen evolution reaction applications, respectively. The excellent photocatalytic and electrochemical activity stems from the synergy between tailored ALD loading of MoSe2 nanosheets on 1D TiO2 nanotubular structure with high surface/volume ratio, which provided fast electron transfer and easy access to the MoSe2 active edges, boosting the catalytic activity.
Depozice atomárních vrstev MoSe2 nanodestiček na povrch TiO2 nanotrubek, fotokatalytický rozklad barviv a elektrokatalytický vývoj vodíku na těchto površích
Keywords: MoSe2; nanosheets; atomic layer deposition; TiO2 nanotube layers; catalysis; MoSe2; nanodestičky; depozice atomárních vrstev; TiO2 nanotrubicové vrstvy; katalýza